From micro- to macroevolution: insights from a Neotropical bromeliad with high population genetic structure adapted to rock outcrops - Mota, Mateus Ribeiro [UNESP]; Pinheiro, Fabio; Santos Leal, Barbara Simoes dos; Sardelli, Carla Haisler; Wendt, Tania; Palma-Silva, Clarisse [UNESP] (Nature Publishing Group, 2020)
Geographic isolation and reduced population sizes can lead to local extinction, low efficacy of selection and decreased speciation. However, population differentiation is an essential step of biological diversification. In allopatric speciation, geographically isolated populations differentiate and persist until the evolution of reproductive isolation and ecological divergence completes the speciation process.Pitcairnia flammeaallows us to study the evolutionary consequences of habitat fragmentation on naturally disjoint rock-outcrop species from the Brazilian Atlantic Rainforest (BAF). Our main results showed low-to-moderate genetic diversity within populations, and deep population structuring caused by limited gene flow, low connectivity, genetic drift and inbreeding of long-term isolation and persistence of rock-outcrop populations throughout Quaternary climatic oscillations. Bayesian phylogenetic and model-based clustering analyses found no clear northern and southern phylogeographic structure commonly reported for many BAF organisms. Although we found two main lineages diverging by similar to 2 Mya during the early Pleistocene, species' delimitation analysis assigned most of the populations as independent evolving entities, suggesting an important role of disjoint rock outcrops in promoting high endemism in this rich biome. Lastly, we detected limited gene flow in sympatric populations although some hybridization and introgression were observed, suggesting a continuous speciation process in this species complex. Our data not only inform us about the extensive differentiation and limited gene flow found amongPitcairnia flammeaspecies complex, but they also contain information about the mechanisms that shape the genetic architecture of small and fragmented populations of isolated rock outcrop of recently radiated plants.